Two pot and one pot synthesis of dipyrazolopyridines derivatives and applications - Saba, Farooq; Zainab, Ngaini (Springer Nature, 2025)
Dipyrazolopyridines (DPPs) are distinctive heterocyclic compounds with broad applications in pharmaceutical and industrial fields. DPPs can be conveniently synthesised using commonly available reagents such as ethyl acetoacetate, hydrazine derivatives, ammonium hydroxide, and aldehyde derivatives. This review article explores the synthesis of DPP derivatives, highlighting various synthetic methods. Two-pot and one-pot synthesis of DPPs and their extensive applications in pharmaceuticals, material synthesis and environmental chemistry have also been comprehensively discussed. The current challenges and prospects of DPPs in various fields have also been emphasised due to the potential technological advancements and demand.